Integrasi Unggas-Lele Berbasis Siklus Nutrisi untuk Penguatan Kemandirian Pangan Rumah Tangga di Desa Purwosari, Kabupaten Nagan Raya, Aceh - Mardliyah, Zahra Rodliyatam; Nada, Salma Alfina Putri; Nasution, Azrina Sufi; Kusumawardani, Eva Flourentina; Emil, Muhammad Farhan Putra; Sartika, Dewi; Damela, Putri (Universitas Insan Cendekia Mandiri, 2026)
This community service program aims to strengthen household food independence in Purwosari Village, Nagan Raya Regency, Aceh Province, through the implementation of an Integrated Farming system that combines poultry rearing and household-scale catfish cultivation. Integration is achieved through a circular nutrient flow mechanism, where poultry manure is processed into organic fertilizer for plants. At the same time, nutrient-rich catfish pond water is utilized as a fertilizer for home gardens. Home garden plants play a role as a nutrient-cycle connector, where crop residues and household organic waste are reused as alternative feed for poultry and catfish, thereby forming a zero-waste production system. Activities were carried out through socialization, technical training, and mentoring for 25 members of the Women Farmers Group (KWT) and 6 health cadres. Program implementation showed an improvement in participants’ understanding, as evidenced by a rise in average scores from 45% on the pre-test to 90% on the post-test. Additionally, this program successfully facilitated the availability of independent family protein sources and increased the efficiency of backyard waste utilization. Overall, the systematic integration of poultry and catfish demonstrates a practical model for strengthening food security and developing family economies at the village level.